2015
DOI: 10.1111/ans.13329
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin therapy for chronic anal fissures: where are we at currently?

Abstract: Botox is an effective strategy for CAF. Low doses can be given with good efficacy as highlighted by our audit and has the potential for great cost saving. The best predictor of recurrence is the presence of pain at the first post-procedure visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
1
8
0
5
Order By: Relevance
“…Human casualties due to botulinum toxin are reported every year. On the other hand, botulinum toxin is used to treat several diseases including strabismus, urinary incontinence, anal fissure, cervical dystonia, migraine headaches [4][5][6][7][8], and a variety of other diseases [9]. Botulinum toxin is also one of the most commonly used materials in the field of plastic surgery, constituting a billion-dollar industry [10].…”
Section: Introductionmentioning
confidence: 99%
“…Human casualties due to botulinum toxin are reported every year. On the other hand, botulinum toxin is used to treat several diseases including strabismus, urinary incontinence, anal fissure, cervical dystonia, migraine headaches [4][5][6][7][8], and a variety of other diseases [9]. Botulinum toxin is also one of the most commonly used materials in the field of plastic surgery, constituting a billion-dollar industry [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our cases, the most inadequate treatment ndings were detected both in Gp A and Gp B in the rst week after treatment (Table 3).Daf et al stated in their study on 101 patients that the most important symptom of relapse cases was that the pain did not pass and that this occurred during the rst patient control [21].…”
Section: Discussionmentioning
confidence: 53%
“…In the literature, there are a few studies investigating factors related with recurrence after BT application. 19,20 These studies revealed that persisting pain after 30 days and the lack of high anal tone were associated with recurrence. In a randomized controlled trial of 99 patients in Iran in 2015, the results of LIS and topical diltiazem + BT were compared.…”
Section: Discussionmentioning
confidence: 99%